CORRELATION BIOMECHANICAL METHOD OF MANUAL MATERIAL HANDLING WITH LOW BACK PAIN - I Putu Sudayasa; Muhammad Idris Ibnu I; Mario Polo Widjaya (Universitas Muhammadiyah Semarang, 2017)
Low back pain is feeling of pain in the lumbosacral and sacroiliac region, often spreading to the upper and lower limbs. Manual material handling (MMH) is still needed because it can be done in the limited space and dependent of physical activity. If MMH is not ergonomically used, it would cause tissue damage, due to excessive lifting load. The aimed of research is to determine the relationship of manual material handling with low back pain. The study design was observational analytic with cross sectionalapproach. Population were all of unloading workers in the Marine Nusantara Port, Kendari, as many as 268 people. The purposive sampling technique was used to recruit 120 respondents. Data was analyzed using Chi Square test, as well as alternative of Kolmogorov-Smirnov test. Results of study showed a correlation between manual material handling with the incidence of low back pain (p= 0.003). The other risk factor, such as age (p= 0.537), smoking (p = 0.988 ), exercise habits (p= 0.854), overweight (p=0.306) did not significantly correlated with low back pain. It can be concluded that manual material handling is the determinant factor of low back pain, among Marine Nusantara Port, Kendari. Key Words: manual material handling, biomechanical methodes, low back pain, unloading workers, physical activity, Nusantara Marine Port